Experiences of Mothers in the Implementation of Breast Pump Use for Breast Health in Somawangi Village, Mandiraja, Banjarnegara - Sri Watini; Rakhmat Susilo (Proceedings Series on Health & Medical Sciences, 2026)
The use of breast pumps plays a crucial role in supporting breastfeeding, especially for working mothers or those facing challenges with direct breastfeeding. However, the effectiveness of breast pump use and its impact on breast health in rural areas remains under-researched. A qualitative descriptive approach was used, involving in-depth interviews with 15 mothers who have used breast pumps. Thematic analysis was performed to identify key themes regarding the experiences of the participants. The results indicated that most mothers had positive experiences with breast pumps, reporting convenience and improved milk expression. However, challenges such as discomfort, lack of knowledge, and improper usage were identified. The study found that breast pump use improved breast health for many mothers, but improper use could lead to breast tissue damage. Breast pump use can be beneficial for supporting breastfeeding and improving breast health. However, it is essential to provide proper education and support to ensure its correct use. Programs aimed at enhancing breastfeeding knowledge and supporting breast pump use should be implemented in rural areas.